An experimental study on the efficacy of Sodium Hyaluronate in prevention of postoperative intraperitoneal adhesions - Sagliyan, Aydin; Gunay, Cihan; Han, Mehmet Cengiz; Sakin, Fatih; Hayat, Ali (My University, 2009)
The objective of this study was to assess the efficacy of hyaluronic acid in prevention of intraabdominal adhesions. Adhesion formation is associated with serious postoperative complications, including intestinal obstruction, infertility and chronic pelvic pain. Various medical and operative agents have been used to prevent peritoneal adhesions. Twenty female Albino rats weighing 250-350 g were used in this study. Each rat was anesthetized with 40 mg kg-1 of intramuscular ketamine hydrochloride and 10 mg kg-1 of xyzaline hydrochloride. A lower midline incision, 3 cm in length, was made. As there were not any adhesions in the abdomen, the ileocecal bowel part was rubbed with sterile hydrophile until a serosal hemorrhage was formed and cecum was replaced in conformity with anatomy. Rats were divided equally into 2 groups, the experimental and control group. The experimental group was given 0.5 mL of intraperitoneal hyaluronic acid and the control group was given 0.5 mL of intraperitoneal physiologic solution. The abdominal incision was closed. At 15 days postoperatively, all the rats were euthanized using anesthesia of ether. Rating of adhesions was performed through a bilateral subcostal incision, evaluating the whole intraperitoneal organs and adhesions macroscopically. © Medwell Journals, 2009.
Keywords: Abdomen; Chronic pelvic pain; Hyaluronic acid; Intra-abdominal adhesion; Rat